Earnings quality and financial flexibility: A moderating role of corporate governance - Rashidul Islam; Ziaul Haque; Rehnuma Hoque Moutushi (Cogent Business & Management, 2022)
The aim of this study is primarily to demonstrate how earnings quality is an influential determinant of financial flexibility. Secondly, how earnings quality affects financial flexibility. And finally, to provide evidence of the role of corporate governance between earnings quality and financial flexibility composing overall corporate governance index (CG-INDEX). This study considered unbalanced panel data from the year 2007 to 2020 from the database CSMAR yielding 14,088 firm-year observations. This study used liquidity as the proxy of financial flexibility, and also used a comprehensive index of corporate governance constructed by adopting the principal component analysis and STATA has been used for analyzing data. The study used System GMM regression for analysis and controls endogeneity by applying lag financial flexibility as an instrumental variable. The empirical results reveal that poor earnings quality significantly negatively influences the level of corporate financial flexibility. The results also demonstrate that corporate governance can significantly positively moderate the relationship between earnings quality and financial flexibility. This suggests that when the earnings quality is poor, firms are less likely to be financially flexible in holding liquidity. More specifically, firms with poor earnings quality will reduce their financial flexibility of firms; hence, firms need to provide high-quality earnings in order to be more financially flexible. Earnings quality is an important factor, which led the author to examine how earnings quality influences financial flexibility. Under the views of agency theory and positive accounting theory, poor earnings quality is a source of amplified shareholder's concern of increased informational asymmetry, which may adversely affect the firm's financial flexibility. Conversely, higher earnings quality reduces the information asymmetry which leads to higher financial flexibility. This study provides a way how to achieve financial flexibility with the assistance of corporate governance which is essential to combat financial crises and smooth business operations successfully.The aim of this study is primarily to demonstrate how earnings quality is an influential determinant of financial flexibility. Secondly, how earnings quality affects financial flexibility. And finally, to provide evidence of the role of corporate governance between earnings quality and financial flexibility composing overall corporate governance index (CG-INDEX). This study considered unbalanced panel data from the year 2007 to 2020 from the database CSMAR yielding 14,088 firm-year observations. This study used liquidity as the proxy of financial flexibility, and also used a comprehensive index of corporate governance constructed by adopting the principal component analysis and STATA has been used for analyzing data. The study used System GMM regression for analysis and controls endogeneity by applying lag financial flexibility as an instrumental variable. The empirical results reveal that poor earnings quality significantly negatively influences the level of corporate financial flexibility. The results also demonstrate that corporate governance can significantly positively moderate the relationship between earnings quality and financial flexibility. This suggests that when the earnings quality is poor, firms are less likely to be financially flexible in holding liquidity. More specifically, firms with poor earnings quality will reduce their financial flexibility of firms; hence, firms need to provide high-quality earnings in order to be more financially flexible. Earnings quality is an important factor, which led the author to examine how earnings quality influences financial flexibility. Under the views of agency theory and positive accounting theory, poor earnings quality is a source of amplified shareholder's concern of increased informational asymmetry, which may adversely affect the firm's financial flexibility. Conversely, higher earnings quality reduces the information asymmetry which leads to higher financial flexibility. This study provides a way how to achieve financial flexibility with the assistance of corporate governance which is essential to combat financial crises and smooth business operations successfully.
Keywords: 650; corporate governance; Earnings quality; financial flexibility